1998
DOI: 10.1093/qjmed/91.7.493
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of compulsive behaviour in eating disorders with intermittent ketamine infusions

Abstract: We have previously shown that eating disorders are a compulsive behaviour disease, characterized by frequent recall of anorexic thoughts. Evidence suggests that memory is a neocortical neuronal network, excitation of which involves the hippocampus, with recall occurring by re-excitement of the same specific network. Excitement of the hippocampus by glutamate-NMDA receptors, leading to long-term potentiation (LTP), can be blocked by ketamine. Continuous block of LTP prevents new memory formation but does not af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 6 publications
1
58
0
Order By: Relevance
“…There was also an intriguing study at the University of Cambridge in the UK, in which ketamine was used to treat compulsive behavior in young women with anorexia nervosa with good results, although the publication of this study does not clearly indicate that the clinicians used a psychotherapeutic model (Mills, Park, Manara, & Merriman, 1998.) The study used infusions of ketamine to treat 15 patients with a long history of eating disorder, all of whom were chronic and resistant to several other forms of treatment.…”
Section: Ketamine-enhanced Psychotherapymentioning
confidence: 99%
“…There was also an intriguing study at the University of Cambridge in the UK, in which ketamine was used to treat compulsive behavior in young women with anorexia nervosa with good results, although the publication of this study does not clearly indicate that the clinicians used a psychotherapeutic model (Mills, Park, Manara, & Merriman, 1998.) The study used infusions of ketamine to treat 15 patients with a long history of eating disorder, all of whom were chronic and resistant to several other forms of treatment.…”
Section: Ketamine-enhanced Psychotherapymentioning
confidence: 99%
“…However, some literature exists for ketamine in other psychiatric situations. In an early and rather interesting data collection, Mills et al (1998) administered serial ketamine infusions to eating disordered patients on the theory that an NMDA antagonist would impair abnormal memories that drive eating-related compulsions. Each infusion consisted of intravenous ketamine 20 mg/ h for 10 h, and patients had serial infusions at intervals of 5-21 days.…”
Section: Other Clinical Uses Of Ketamine In Psychiatrymentioning
confidence: 99%
“…In patients with a long history of eating disorder that were resistant to several other forms of treatment, Mills et al . (49) attempted infusions of 20 mg per hour ketamine for 10 h along with 20 mg twice daily nalmefene as opioid antagonist. Nine of 15 patients examined in the study showed prolonged remission when treated with two to nine ketamine‐infusion sessions at intervals of 5 days to 3 weeks.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…Although amygdala circuits deal with a general category of biologically relevant stimuli (noxious, menacing), separate ventromedial prefrontal systems may be activated depending on the perceived social threat or incentive value of activities when abstaining from motivationally salient foods or engaging in obsessive regiment of training (48). Unlike LTP, which models environmental input, fear is capable of being self-perpetuated when amygdala cells are barraged by 'AN thoughts' (49) in individuals with a deficient processing of personal somatic representation rather than by the (objective) assessment of 'others'. Synaptic plasticity may plausibly underlie chronicity of AN, which is its main hazard in terms of medical complications and social consequences.…”
Section: Lost In Translation: Is Anorexia Nervosa a Phobic Disorder?mentioning
confidence: 99%